2007
DOI: 10.1158/0008-5472.can-06-2295
|View full text |Cite
|
Sign up to set email alerts
|

Colon Cancer Cell–Derived Tumor Necrosis Factor-α Mediates the Tumor Growth–Promoting Response in Macrophages by Up-regulating the Colony-Stimulating Factor-1 Pathway

Abstract: The interplay between malignant and stromal cells is essential in tumorigenesis. We have previously shown that colonystimulating factor (CSF)-1, matrix metalloprotease

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 30 publications
5
91
0
2
Order By: Relevance
“…The complex interactions between the neoplastic and inflammatory cells, which are mediated by inflammatory cytokines, are essential features of the tumor microenvironment [14] . Tumor necrosis factor-a (TNF-a) is a proinflammatory cytokine predominantly produced by macrophages as well as tumor cells [15,16] , and is a cytokine ligand of the TNF family that interacts with different receptors of the TNF receptor superfamily. The activity of this system may be one of the drivers of progression in CRC [17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex interactions between the neoplastic and inflammatory cells, which are mediated by inflammatory cytokines, are essential features of the tumor microenvironment [14] . Tumor necrosis factor-a (TNF-a) is a proinflammatory cytokine predominantly produced by macrophages as well as tumor cells [15,16] , and is a cytokine ligand of the TNF family that interacts with different receptors of the TNF receptor superfamily. The activity of this system may be one of the drivers of progression in CRC [17] .…”
Section: Introductionmentioning
confidence: 99%
“…It has multiple effects on cell function by binding to specific high-affinity, cell-surface receptors. Apart from its apoptosis-inducing mechanisms, TNF-a may promote tumor growth at lower levels during cancer progression [15,16] . A mounting body of evidence has suggested that TNF-a mediates many critical processes of tumor progression, including oncogene activation, DNA damage, and tumor metastases [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…TNF has a critical role in the pathogenesis of inflammatory bowel diseases (IBD) and is a therapeutic target for treatment of these disorders (54,67). Furthermore, mounting evidence suggests that TNF signaling is important in the pathogenesis of GI cancers (47,50,78). Specifically, an altered balance between prosurvival and apoptotic signaling stimulated by TNF may be critical for tumorigenesis (5,57).…”
mentioning
confidence: 99%
“…The results seem reasonable because those factors have been thought to be upregulated in vivo in the TME via the activation of macrophages and other immune cells. [34,35] However we confined this study to the tumor fibroblast interaction and compensated for the immune cell derived factors with extrinsic factors in the following experi ments, to limit the complexity of our model system.…”
Section: Angiogenesismentioning
confidence: 99%